Babesia spp. in ticks and wildlife in different habitat types of Slovakia - Hamšíkova, Zuzana (2016)
Background: Babesiosis is an emerging and potentially zoonotic disease caused by tick-borne piroplasmids of the Babesia genus. New genetic variants of piroplasmids with unknown associations to vectors and hosts are recognized. Data on the occurrence of Babesia spp. in ticks and wildlife widen the knowledge on the geographical distribution and circulation of piroplasmids in natural foci. Questing and rodent-attached ticks, rodents, and birds were screened for the presence of Babesia-specific DNA using molecular methods. Spatial and temporal differences of Babesia spp. prevalence in ticks and rodents from two contrasting habitats of Slovakia with sympatric occurrence of Ixodes ricinus and Haemaphysalis concinna ticks and co-infections of Candidatus N. mikurensis and Anaplasma phagocytophilum were investigated. Results: Babesia spp. were detected in 1.5 % and 6.6 % of questing I. ricinus and H. concinna, respectively. Prevalence of Babesia-infected I. ricinus was higher in a natural than an urban/suburban habitat. Phylogenetic analysis showed that Babesia spp. from I. ricinus clustered with Babesia microti, Babesia venatorum, Babesia canis, Babesia capreoli/Babesia divergens, and Babesia odocoilei. Babesia spp. amplified from H. concinna segregated into two monophyletic clades, designated Babesia sp. 1 (Eurasia) and Babesia sp. 2 (Eurasia), each of which represents a yet undescribed novel species. The prevalence of infection in rodents (with Apodemus flavicollis and Myodes glareolus prevailing) with B. microti was 1.3 % in an urban/suburban and 4.2 % in a natural habitat. The majority of infected rodents (81.3 %) were positive for spleen and blood and the remaining for lungs and/or skin. Rodent-attached I. ricinus (accounting for 96.3 %) and H. concinna were infected with B. microti, B. venatorum, B. capreoli/B. divergens, Babesia sp. 1 (Eurasia), and Babesia sp. 2 (Eurasia). All B. microti and B. venatorum isolates were identical to known zoonotic strains from Europe. Less than 1.0 % of Babesia-positive ticks and rodents carried Candidatus N. mikurensis or A. phagocytophilum.